Editorial - Rodríguez, Diana Catalina (Revista Facultad de Ingeniería Universidad de Antioquia, 2019)
Anaerobic digestion has been conceived world wide asa way of sustainable treatment being widely developed around the world, which has allowed the treatment of wastewater not only from the conventional process vision, but also from the removal of recalcitrant pollutants, and the exploitation and use of energy. In Colombia, anaerobic digestion has been fundamental for the development of the country, since it has been the foundation for basic sanitation in rural zones and it has established the guidelines for the treatment of domestic and industrial wastewater. It is also currently used in the management and appropriate disposal of sludge.